Petrogenesis of late triassic high-silica granites in the North Qiangtang terrane, central Tibetan Plateau - Ji, Changjun; Liu, Bin; Chen, Yun; Wu, Zhenhan; Chen, Chong (Frontiers in Earth Science, 2024)
Although high-silica granites can provide unique insights into the maturity of the continental crust and rare metal enrichment, the origin of high-silica granitic magmatism remains uncertain. In this paper, we present an integrated study of zircon U-Pb geochronology and trace elements, whole-rock geochemistry, and Sr-Nd isotopes for two typical high-silica granites (namely, the Longbao granitic porphyry and the Yushu granite) found in the North Qiangtang terrane, central Tibetan Plateau. Zircon geochronological data indicate that these high-silica granites crystallized at 217–214 Ma. All the samples from the Longbao granitic porphyry and the Yushu granite exhibited high SiO2, low MgO, depletion of Ba, Nb, Sr, P, and Ti, and enrichment of Th and U. They exhibited relatively high (87Sr/86Sr)i ratios of 0.7120–0.7136 and low εNd(t) values of −8.58 ∼ −7.58; together with their old ages according to the two-stage Nd model (1.6–1.7 Ga), these features indicate the involvement of crustal materials. Geochemical and isotopic variation indicated that the high-silica granites studied were mainly produced by the dehydration melting of a muscovite (Ms)-bearing source, and that the Triassic turbidites might be a good candidate for the magma source. Combining this evidence with new regional studies, it can be concluded that partial melting of Triassic turbidites induced by slab roll-back might be the key factor controlling the origin of Late Triassic magmatism in the North Qiangtang terrane.